Social Integration and New Realities in the Swedish Welfare Society - Norma Montesino (Social Work & Society, 2011)
This article argues that there is a discrepancy between the perception of social realities held by professionals of welfare (school teachers and social workers) in Sweden and the social realities of migrants, especially migrants depending on social assistance. The views held by professionals are rooted in an old model of social integration within the framework of the nation-state. This perception contrasts with the life conditions, expressed here in the consumption practices of migrant families who, in their daily life, are linked to both local and transnational places. Consumption is an "old question" that has been linked both to poverty and immigration. The article is focusing not on consumption as such; instead on consumption as an illustration of the mismatch existing between the professionals' view and the migrants' description of their own consumption. The analysis is based on a qualitative study including interviews with migrant families and welfare officers in a neighbourhood in Malmoe, a city in the South of Sweden with some 300,000 inhabitants, of which 29 % are born outside Sweden.